Systematic Literature Review (SLR): Analisis Isu Mental Health Di Era Digital - Gunawan Putra Wahdana; Dhimas Tribuana; Dayanti Dayanti (Plexi Digital Indonesia, 2026)
Mental health has become a critical global issue that has significantly increased in recent years, driven by social changes and the rapid development of digital technology. This study aims to identify key domains, analyze research trends, and uncover research gaps in mental health studies using a Systematic Literature Review (SLR) approach. The methodology involves identification, screening, eligibility assessment, and in-depth analysis of 20 scientific articles published between 2023 and 2026. The results reveal four main domains in mental health research: service accessibility, technology and artificial intelligence, social factors, and global collaboration. The findings indicate that although technologies such as Artificial Intelligence (AI) and machine learning improve prediction accuracy and early detection, the primary challenges remain in limited access to mental health services and the influence of social factors. Furthermore, a gap exists between technological development and real-world implementation. The main contribution of this study is the development of an integrative mental health system model that combines access, technology, social factors, and collaboration. This model is expected to serve as a foundation for developing more effective, integrated, and sustainable mental health systems in the future.